2012
DOI: 10.1017/s1368980012002947
|View full text |Cite
|
Sign up to set email alerts
|

Year-round vitamin D deficiency among Saudi female out-patients

Abstract: AbstractObjectiveThe aim of the present study was to investigate vitamin D status among female out-patients in Saudi Arabia during the summer and winter seasons.DesignData were retrospectively collected using medical record abstraction. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…Most studies on vitamin D deficiency and insufficiency among the elderly in the Middle East have been conducted on women [26,45,46,47,48], a few have included both genders [11,15,49,50], and only one has been conducted solely on men [12]. Low prevalence of vitamin D deficiency has been reported among the elderly in Egypt at 19.3% [12] and KSA at 23.1% [23]; however, insufficiency levels were found to be higher, reaching 41% among the elderly in Lebanon [15] and 77.2% among those in Egypt [26].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on vitamin D deficiency and insufficiency among the elderly in the Middle East have been conducted on women [26,45,46,47,48], a few have included both genders [11,15,49,50], and only one has been conducted solely on men [12]. Low prevalence of vitamin D deficiency has been reported among the elderly in Egypt at 19.3% [12] and KSA at 23.1% [23]; however, insufficiency levels were found to be higher, reaching 41% among the elderly in Lebanon [15] and 77.2% among those in Egypt [26].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Several observational studies from the KSA have reported a prevalence of vitamin D insufficiency (serum 25(OH)D < 50 nmol/L) in the range of 19%–85% in postmenopausal women [42,46,47,48]. For example, in a cohort of 671 postmenopausal women, Ardawi et al found 34.1% of women presented with vitamin D insufficiency (serum 25(OH)D < 50 nmol/L) and secondary parathyroidism evident in 24.6% of women, with lower vitamin D status and higher intact parathyroid hormone in the upper quintiles of BMI and waist-to-hip ratio [48].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Thus in winter the people had worse vitamin D status. But even in summer, the mean concentration of 25(OH)D in the study population was only 25.6 ng/ml, with about 1/4 being hypovitaminosis D. The situation was similar to that of female adults in Saudi Arabia [18], which was at lower latitude than Shanghai. Even in Thailand, a tropical country, the prevalence of vitamin D deficiency in adolescents was up to 10% [19].…”
Section: Discussionmentioning
confidence: 48%
“…Several large-sample populations-based studies as well as smaller studies also revealed a high prevalence of hypovitaminosis D and of rickets in infants (0.5% of Saudis <2 years) and adolescents in Saudi Arabia (21,22,23,24,25,30). …”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence also shows the extra-skeletal benefits of vitamin D, such as those on the immune system, fuel metabolism, cardiovascular system, and cancer. In addition, associations with decreased mortality have been reported (13,17,18,19,20,21,22,23,24,25,26,27,28,29). …”
Section: Discussionmentioning
confidence: 99%